Total Oxidation of CO Using Cu & Co Catalyst: Kinetic Study and Calcinations Effect - Gaurav Rattan; Rajwant Kaur (Bulletin of Chemical Reaction Engineering & Catalysis, 2015)
The present study deals with the oxidation of CO using base metal catalysts. A series of copper cobalt with different mole ratios were prepared by wet-impregnation method calcined at 400 oC for 3 h for the oxidation of CO. The mole ratios were varied from 1:1 to 1:5 by varying the weight of nitrates accord-ingly. It was found that 1:3 and 1:4 are active catalyst among the other prepared catalysts. Further, the two catalysts (1:3 & 1:4) were prepared by co-precipitation and citric sol-gel methods in order to see the effect of preparation method. The results showed that the catalyst prepared by co-precipitation method is good in terms of activity for CO oxidation. The best selected catalyst was characterized by TGA/DSC and XRD. Kinetic study was also performed on the selected catalyst. Copyright © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).